Composite current collector base film, method for producing the same, composite current collector, electrode sheet, and electrochemical device
Patent Information
- Application Number
- CN202611335457.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-27
AI Technical Summary
本发明通过利用聚对苯二甲酸丁二醇酯、聚对苯二甲酸丙二醇酯、聚对苯二甲酸乙二醇酯醇链段中亚甲基数量(n=4、3、2)的递变,构建了快—中—慢三级结晶速率体系,配合铸片、拉伸、热定型的工艺顺序,实现了大尺寸球晶、中等尺寸环带晶和小尺寸片晶在不同时间窗口、不同空间区位的原位分级生成,避免了晶体间的无序竞争,确保了晶体尺寸比的稳定可控。其中,聚对苯二甲酸丁二醇酯优先在铸片阶段无约束空间下充分结晶,分子链可沿径向自由生长,从而形成大尺度球晶;进入拉伸和热定型阶段后,聚对苯二甲酸丙二醇酯、聚对苯二甲酸乙二醇酯开始大量结晶。此时,聚对苯二甲酸丙二醇酯因具有奇碳效应的螺旋弹簧构象,在应力作用下先于聚对苯二甲酸丁二醇酯取向并结晶。由于聚对苯二甲酸丁二醇酯大球晶已占据宏观空间,聚对苯二甲酸丙二醇酯只能在球晶间隙中结晶且结晶尺寸受限于取向网络;同时,拉伸剪切力迫使球晶内部的片晶发生周期性扭转,形成同心圆环状起伏的中尺度环带晶;聚对苯二甲酸乙二醇酯因链段刚性最大、结晶速率最慢,生长空间受限,聚对苯二甲酸乙二醇酯只能在球晶和环带晶空隙以及晶体界面上以高度取向的小尺寸片晶形式析出。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of current collector technology, and in particular to a base film for a composite current collector, its preparation method, the composite current collector, electrode sheet, and electrochemical device. Background Technology
[0002] Composite current collectors are a novel type of composite material made by depositing metal layers on both sides of a polymer film (such as polyester) using a vacuum deposition process. The composite current collector employs a sandwich structure of metal layer-polymer-metal layer, offering significant weight reduction advantages compared to traditional metal foils. Due to the reduced weight percentage and increased proportion of active materials within the battery, composite current collectors can effectively improve battery energy density. Furthermore, polymer materials are highly resistant to breakage; the elongation at break of composite current collectors can reach 35%, far exceeding that of conventional metal foils. Based on these advantages, composite current collectors have become an important development direction in the field of lithium-ion battery current collectors.
[0003] With the continuous upgrading of battery life in 3C digital products and new energy electric vehicles, especially the increasing compaction density of lithium-ion battery cathode sheets, lithium cobalt oxide, as the mainstream cathode material in high-end consumer electronics, and composite aluminum foil, as a key current collector material in the lithium cobalt oxide system, require the intermediate polyester film to withstand severe Z-axis pressure under the molding pressure corresponding to this high compaction density. Under this immense pressure, significant shear stress is generated within the polyester film. When this shear stress exceeds the mechanical tolerance limit of the polyester film, it directly leads to deformation and breakage, severely affecting the encapsulation integrity of the composite aluminum foil, and consequently causing performance degradation and safety hazards in the lithium cobalt oxide electrode. This issue has become a core technological bottleneck restricting the application of composite aluminum foil in high-compact-density lithium cobalt oxide systems.
[0004] In existing composite current collectors, the polyester film and metal layer are mainly bonded by intermolecular forces (such as van der Waals forces). This bonding method has the following shortcomings: 1. Insufficient interfacial adhesion: The contact area between the polyester film surface and the metal layer is limited, and the interfacial adhesion strength mainly relies on physical adsorption, lacking an effective "anchoring" structure. Under the enormous shear stress generated during high-pressure compaction rolling, interfacial debonding easily occurs between the metal layer and the polyester film.
[0005] 2. Insufficient mechanical buffering and stress dispersion capabilities: Existing polyester films lack sufficient mechanical buffering performance. Under the strong stress generated by high compaction, polyester films cannot effectively disperse or absorb stress energy, and can only passively withstand shear forces, leading to frequent deformation problems.
[0006] 3. Mismatch between the ductility of the metal layer and the polyester film: There is a difference in ductility between the metal layer and the polyester film. During the rolling process, when the electrode is subjected to the huge deformation corresponding to the high compaction density, the incoordination of deformation between the metal layer and the polyester film will generate interfacial shear stress, further aggravating the risk of aluminum layer deformation and interfacial debonding.
[0007] In view of this, the present invention is hereby proposed. Summary of the Invention
[0008] The purpose of this invention is to provide a base film for composite current collectors, a method for preparing the same, a composite current collector, an electrode sheet, and an electrochemical device, in order to solve at least one of the above-mentioned technical problems.
[0009] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: In a first aspect, the present invention provides a base film for composite current collectors, the base film comprising a surface layer and a core layer, the surface layer comprising a blend of at least two of polybutylene terephthalate, polypropylene terephthalate, and polyethylene terephthalate; the core layer comprising at least one of polybutylene terephthalate, polypropylene terephthalate, and polyethylene terephthalate; the preparation of the base film comprises sequentially performing a casting process, a stretching process, and a heat setting process; The polybutylene terephthalate crystallizes to form spherulites during the casting process, the polypropylene terephthalate crystallizes to form banded crystals during the stretching and heat-setting processes, and the polyethylene terephthalate crystallizes to form lamellar crystals during the stretching and heat-setting processes; the crystal size ratio of the spherulites, banded crystals, and lamellar crystals is (10-100):(1-20):1; at least two of the spherulites, banded crystals, and lamellar crystals at least partially protrude from the surface of the surface layer to form an uneven structure.
[0010] Furthermore, in the casting process, polybutylene terephthalate has at least 35% crystallinity, and polypropylene terephthalate and / or polyethylene terephthalate have less than 3% crystallinity; and / or, In the stretching treatment and the heat setting treatment, the polypropylene terephthalate and the polyethylene terephthalate have a crystallinity of at least 50%; and / or, The crystal structure formed by the crystallization of polybutylene terephthalate is a spherulite with an n_PBT ratio of 3-4, and a crystal size of 1μm-5μm; and / or, The crystal structure formed by the crystallization of polypropylene terephthalate is a ring-zoned crystal with an n_PTT of 2-3, and the crystal size is 100nm-1000nm; The crystal structure formed by the crystallization of polyethylene terephthalate is a lamellar crystal with n_PET of 1.5-2.5 and a crystal size of 50nm~100nm.
[0011] Furthermore, in the surface layer, the mass ratio of polybutylene terephthalate to polypropylene terephthalate is 1:(0.15-6); and / or, The mass ratio of polybutylene terephthalate to polyethylene terephthalate is 1:(1-18); and / or, the mass ratio of polypropylene terephthalate to polyethylene terephthalate is 1:(1-18).
[0012] Furthermore, the surface layer is a ternary blend of polybutylene terephthalate, polypropylene terephthalate, and polyethylene terephthalate; and / or, The surface layer includes a first surface layer and a second surface layer, the thickness of which is independently 10%-20% of the thickness of the base film; and / or, The thickness of the base film is 2μm~15μm; and / or, The surface layer also includes 0.1% to 1.0% antioxidant by weight of the surface layer; and / or, The surface layer further includes a heat stabilizer comprising 0.1% to 1.0% of the surface layer mass; and / or, The core layer also includes an antioxidant comprising 0.1% to 1.0% of the core layer mass.
[0013] Furthermore, the surface layer comprises, by 100% by mass, 5%-30% of polybutylene terephthalate, 5%-30% of polypropylene terephthalate, and 40%-85% of polyethylene terephthalate.
[0014] Secondly, the present invention provides a method for preparing a base film for a composite current collector, the method comprising the following steps: At least two of polybutylene terephthalate, polypropylene terephthalate and polyethylene terephthalate are mixed evenly in proportion and used as the raw material for the surface layer, and then melted to obtain the surface melt. At least one of polybutylene terephthalate, polypropylene terephthalate and polyethylene terephthalate is used as the core layer material, and then melted to obtain the core layer melt. Then, the surface melt and the core melt are co-extruded in three layers and then sequentially subjected to casting, stretching and heat setting to obtain the composite current collector base film. The surface melt includes a first surface melt and a second surface melt; polybutylene terephthalate is crystallized in the casting process; and polypropylene terephthalate and polyethylene terephthalate are crystallized in the stretching and heat setting processes.
[0015] Furthermore, the casting process includes cooling the co-extruded melt to a temperature range of 110°C-130°C at a cooling rate of 50°C / min-100°C / min, holding it at that temperature for 5s-15s to achieve a crystallinity of polybutylene terephthalate of 35% or higher; and / or, In the casting process, the semi-crystallization time of polybutylene terephthalate is 0.2s-1s, that of polypropylene terephthalate is 5min-40min, and that of polyethylene terephthalate is 3min-30min; and / or, In the stretching process, the semi-crystallization time of the polypropylene terephthalate is 10 min-60 min, the semi-crystallization time of the polyethylene terephthalate is 5 min-45 min, and the semi-crystallization time of the polybutylene terephthalate is 0.2 s-1 s; and / or, In the heat setting treatment, the semi-crystallization time of the polypropylene terephthalate is 0.5 min to 4 min, the semi-crystallization time of the polyethylene terephthalate is 0.2 min to 2 min, and the semi-crystallization time of the polybutylene terephthalate is 0.1 min to 1 min.
[0016] Furthermore, before melting, the first surface layer material, the core layer material, and the second surface layer material are dried to ensure that the moisture content of the surface layer material and the core layer material is less than 50 ppm. Preferably, the drying temperature of the polybutylene terephthalate is 120℃~140℃, and the drying time is 4 hours~8 hours; Preferably, the drying temperature of the polypropylene terephthalate is 110℃~130℃, and the drying time is 4 hours~8 hours; Preferably, the drying temperature of the polyethylene terephthalate is 140℃~160℃, and the drying time is 4 hours~8 hours.
[0017] Furthermore, the melting temperature of the surface layer is 240℃~265℃; Preferably, the melting temperature of the core layer is 265℃~280℃; Preferably, the extrusion temperature of the three-layer co-extrusion is 260℃~275℃; Preferably, the casting process further includes casting the semi-finished product of polybutylene terephthalate after full crystallization onto a quenching roller for quenching to obtain a casting sheet; Preferably, the temperature of the quenching roller is 15°C to 40°C; Preferably, in the stretching process, the longitudinal stretching ratio is 2.5 to 4.0 times, and the transverse stretching ratio is 3.0 to 5.0 times; Preferably, in the stretching process, the longitudinal stretching temperature is 45℃~80℃, and the transverse stretching temperature is 85℃~120℃. Preferably, the heat setting process includes holding the stretched film semi-finished product at a constant temperature of 160°C to 190°C for 20 to 150 seconds to obtain a base film.
[0018] Thirdly, the present invention provides a composite current collector, the composite current collector comprising a base film and a metal layer disposed on at least one surface of the base film; the base film is the composite current collector base film described above or the composite current collector base film prepared by the preparation method described above.
[0019] Fourthly, the present invention provides an electrode sheet comprising the aforementioned composite current collector.
[0020] Fifthly, the present invention provides an electrochemical device including the aforementioned electrode sheet.
[0021] Compared with the prior art, the present invention has at least the following beneficial effects: This invention utilizes the varying number of methylene groups (n=4, 3, 2) in the alcohol segments of polybutylene terephthalate (PET), polypropylene terephthalate (PPT), and polyethylene terephthalate (PET) to construct a fast-medium-slow three-level crystallization rate system. Combined with the process sequence of casting, stretching, and heat setting, this achieves in-situ hierarchical generation of large-sized spherulites, medium-sized zoned crystals, and small-sized lamellar crystals at different time windows and spatial locations, avoiding disorderly competition between crystals and ensuring stable and controllable crystal size ratios. Specifically, PET preferentially crystallizes fully in the unconstrained space during the casting stage, allowing the molecular chains to grow freely radially, thus forming large-scale spherulites. Upon entering the stretching and heat setting stages, PPT and PET begin to crystallize in large quantities. At this point, PPT, due to its helical spring conformation with a unique carbon effect, orients and crystallizes before PET under stress. Because the large spherulites of polybutylene terephthalate occupy the macroscopic space, polypropylene terephthalate can only crystallize in the interspherulites and its crystal size is limited by the orientation network. At the same time, the tensile shear force forces the lamellar crystals inside the spherulites to undergo periodic torsion, forming concentric ring-shaped undulating medium-scale ring crystals. Polyethylene terephthalate, due to its highest chain segment rigidity and slowest crystallization rate, has limited growth space and can only precipitate in the form of highly oriented small lamellar crystals in the gaps between spherulites and ring crystals, as well as on the crystal interface.
[0022] Furthermore, the multi-level uneven structure formed by at least partially protruding crystals of three specific sizes and shapes can significantly improve the interfacial bonding between the base film and the metal layer, enabling the base film to maintain a high elastic modulus while also having excellent elongation at break, and to withstand the high pressure and repeated bending of the subsequent rolling process of the composite current collector without cracking. Among them, the spherulites formed in the crystal structure have good flexibility and will undergo elastic compression or deformation under stress, making them less prone to stress cracking. They form a flexible skeleton for the base film and provide a deep anchoring effect. During metal coating, molten metal penetrates into the "valleys" formed by the spherulites and forms a "rivet" effect after cooling, which significantly improves the peel strength. The annular crystals have anisotropic deformation capabilities. When the film is subjected to bending or transverse shear force, the annular structure converts the shear stress into circumferential dissipation energy through elastic deformation, which significantly improves the crack resistance of the base film. At the same time, it provides annular grooves and ridges. This periodic morphology can effectively increase the contact perimeter between the metal layer and the base film and use the directionality of the annular bands to resist multiaxial shear stress, preventing the metal layer from wrinkling and falling off when bent. Rigid lamellar structures can be densely embedded in the interstices of spherulites or zonal crystals, providing sufficient mechanical support while also providing nanoscale roughness and polar sites. The edges of the lamellars contain a large number of chain folds and end-group defects, which are highly chemically active and can enhance the wettability and nucleation density during metal atom deposition, thus avoiding the formation of a loose "island-like" structure in the metal layer. Detailed Implementation
[0023] The embodiments and examples of the present invention will be described in detail below with reference to the implementation methods and examples. However, those skilled in the art will understand that the following implementation methods and examples are only for illustrating the present invention and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0024] The first aspect of the present invention provides a base film for composite current collectors, the base film comprising a surface layer and a core layer, the surface layer comprising a blend of at least two of polybutylene terephthalate (PBT), polypropylene terephthalate (PTT), and polyethylene terephthalate (PET); the core layer comprising at least one of polybutylene terephthalate (PBT), polypropylene terephthalate (PTT), and polyethylene terephthalate (PET); the preparation of the base film comprises sequentially performing a casting process, a stretching process, and a heat setting process; The polybutylene terephthalate crystallizes to form spherulites during the casting process, the polypropylene terephthalate crystallizes to form banded crystals during the stretching and heat-setting processes, and the polyethylene terephthalate crystallizes to form lamellar crystals during the stretching and heat-setting processes; the crystal size ratio of the spherulites, banded crystals, and lamellar crystals is (10-100):(1-20):1; at least two of the spherulites, banded crystals, and lamellar crystals at least partially protrude from the surface of the surface layer to form an uneven structure.
[0025] The composite current collector base film provided by this invention achieves ordered stepwise crystallization of each component at different process stages and spatial positions by constructing a gradient structure with a surface layer composed of at least two of PBT / PTT / PET and a core layer composed of at least one of PBT / PTT / PET, combined with casting, stretching, and heat setting processes. Specifically, PBT preferentially crystallizes in the casting stage to form micron-sized spherulites, while PTT and PET crystallize in the subsequent stretching and heat setting stages to form submicron-sized ring crystals and nano-sized lamellar crystals, respectively. The three types of crystals are generated in situ in a specific ratio of (10-100):(1-20):1, with at least two types of crystals protruding from the surface layer to collaboratively construct an uneven structure. "10-100" can be, for example, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, etc., and "1-20" can be, for example, 1, 5, 10, 15, 20, etc. If the crystal size ratio is less than the lower limit of 10:1:1, the gaps between spherulites cannot be effectively filled by subsequent zoned crystals and lamellar crystals, leaving micron-sized macroscopic voids. During metal deposition, these voids become weak areas, causing the metal layer to collapse or fail to bridge. If the crystal size ratio is greater than the upper limit of 100:20:1, the spherulites will squeeze the surrounding space, causing the growth space of zoned crystals (PTT) to be severely compressed (below 1), losing the buffer layer; at the same time, if the zoned crystal ratio exceeds 20, it will excessively squeeze the filling space of the nanosheet crystals, making the base film surface too smooth and losing nanoscale chemical anchoring points.
[0026] Further explanation: By utilizing the 2 / 3 / 4 methylene groups in the alcohol segments of PBT, PTT, and PET, a clear crystallization rate gradient is achieved (PBT > PTT > PET). Simultaneously, through the separation and design of the casting, stretching, and heat-setting process steps, PBT preferentially and fully crystallizes during the casting stage, while the crystallization of PTT and PET is delayed until the stretching and heat-setting stages, thus achieving a phased and controllable three-stage crystallization sequence. Specifically, this allows the three components to crystallize sequentially and in stages during preparation: PBT crystallizes first to form a primary uneven structure, PTT subsequently crystallizes to further enrich the morphology at the mesoscale, and PET crystallizes last to fill and refine the surface structure at the nanoscale. The three components, PET, PTT, and PBT, exhibit good compatibility in their amorphous state, exhibiting glass transition temperatures dependent on individual components. This ensures that the ternary blend forms a homogeneous mixture during melt extrusion, avoiding macroscopic phase separation. Although the three components are compatible in their amorphous state, during melt crystallization, each component crystallizes separately, forming its own crystals. This compatible yet independently crystallizing characteristic allows the three components to maintain system homogeneity while each exhibiting its own crystallization properties, jointly constructing multi-scale morphologies.
[0027] In some preferred embodiments, during the casting process, polybutylene terephthalate has at least 35% crystallinity, and polypropylene terephthalate and / or polyethylene terephthalate has less than 3% crystallinity. During the stretching and heat-setting processes, the polypropylene terephthalate and polyethylene terephthalate have at least 50% crystallinity.
[0028] In this invention, by controlling the casting process, the crystallinity of PBT is made to reach ≥35%, while the crystallinity of PTT and / or PET is <3%, thereby pre-constructing a stable micron-scale spherulite skeleton on the surface. Subsequently, in the stretching and heat setting stage, the synergistic effect of stress and temperature is used to promote the rapid crystallization of PTT and PET to ≥50%, causing the directional precipitation of ring-shaped crystals and lamellar crystals in the spherulite gaps and on the surface. The crystallinity gradient in these two stages is the process guarantee for achieving the spatial hierarchical arrangement of the three types of crystals and the controllable formation of cross-scale concave and convex morphology.
[0029] In some preferred embodiments, the crystal structure formed by the crystallization of polybutylene terephthalate is a spherulite with n_PBT of 3-4 and a crystal size of 1μm-5μm, such as 1μm, 2μm, 3μm, 4μm, 5μm, etc. The crystal structure formed by the crystallization of polypropylene terephthalate is a banded crystal with n_PTT of 2-3 and a crystal size of 100nm-1000nm, such as 100nm, 550nm, 1000nm, etc. The crystal structure formed by the crystallization of polyethylene terephthalate is a lamellar crystal with n_PET of 1.5-2.5 and a crystal size of 50nm~100nm, such as 50nm, 75nm, 100nm, etc.
[0030] Furthermore, these three dimensions of crystals can be well stacked in an alternating manner along the thickness and horizontal directions of the base film to form a composite crystal structure. Among them, spherulites with n_PBT (dimension 3-4) protrude from the base film surface, forming large-scale dome-shaped protrusions and deep valleys, serving as the main framework of the surface morphology. This dimension of crystal structure acts as physical anchor points during metal plating, penetrating deep into the metal layer and significantly improving resistance to vertical pull-out peeling. Furthermore, the periodic concentric ridges and annular grooves formed on the surface of the annular crystals with n_PTT (dimension 2-3) are superimposed between or on the surface of the spherulites, exhibiting moderate scale and anisotropic characteristics. This mesoscale undulation effectively converts the shear stress parallel to the film surface experienced by the metal layer into circumferential dissipative deformation, significantly improving the crack resistance of the base film and metal layer under repeated bending conditions. Furthermore, nanoscale lamellar crystals with an n_PET (dimension) of 1.5-2.5 are densely packed in the gaps and surfaces between spherulites and zonal crystals, forming numerous nanoscale peaks, steps, and grooves at their edges. This dimensional crystal structure significantly increases the interfacial contact area with the metal layer. Simultaneously, the capillary effect of the nano-pits guides the preferential condensation and nucleation of metal vapor. The numerous chain end groups and polar ester groups exposed at the lamellar edges provide high-density chemical affinity sites for metal atoms, enhancing the initial nucleation density and wettability of the metal layer. Based on the synergistic effect of the aforementioned chain segment design and staged crystallization, this invention ultimately constructs a multi-dimensional composite concave-convex structure with a vertical gradient distribution and horizontal interlocking on the surface of the base film. This achieves high-strength mechanical interlocking and high-density nucleation adhesion between the metal layer and the base film, effectively solving the long-standing technical problems of poor interfacial adhesion and metal layer detachment after bending in the field of composite current collectors.
[0031] In some preferred embodiments, the surface layer includes a first surface layer and a second surface layer. In this invention, the base film adopts a three-layer co-extrusion structure, which consists of a first surface layer, a core layer, and a second surface layer stacked together; wherein the first surface layer and the second surface layer symmetrically cover the upper and lower sides of the core layer, together forming a double-sided functionalized surface layer structure.
[0032] In some preferred embodiments, the thickness of the first and second surface layers is independently 10%-20% of the thickness of the base film, for example, it can be 10%, 15%, 20%, etc.
[0033] In some preferred embodiments, the thickness of the base film is 2μm to 15μm, for example, it can be 4μm, 6μm, 8μm, 10μm, 12μm, 14μm, 15μm, etc.
[0034] In some preferred embodiments, when the surface layer is composed of polybutylene terephthalate and polypropylene terephthalate as blending components, the mass ratio of polybutylene terephthalate to polypropylene terephthalate is 1:(0.15-6), for example, it can be 1:0.15, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, etc.
[0035] When the surface layer is composed of polybutylene terephthalate and polyethylene terephthalate as blending components, the mass ratio of polybutylene terephthalate and polyethylene terephthalate is 1:(1-18), for example, it can be 1:1, 1:5, 1:10, 1:15, 1:18, etc.
[0036] When the surface layer is composed of polypropylene terephthalate and polyethylene terephthalate, the mass ratio of polypropylene terephthalate to polyethylene terephthalate is 1:(1-18), for example, it can be 1:1, 1:5, 1:10, 1:15, 1:18, etc.
[0037] The component ratio design in this invention takes into account both the matching of crystallization kinetics and the adjustability of morphology. When the PBT content is high, it is conducive to the full growth of spherulites and the protrusion of the surface. When the PTT or PET content is increased, the ability to form ring crystals or the density and thermal stability of lamellar crystals are enhanced, respectively. Thus, a cross-scale concave-convex structure with multi-level mechanical interlocking function can be stably constructed under different process windows.
[0038] More preferably, the surface layer is a ternary blend of polybutylene terephthalate, polypropylene terephthalate, and polyethylene terephthalate.
[0039] The surface layer, calculated as a 100% mass percentage, comprises: The mass percentage of polybutylene terephthalate is 5%-30%, for example, it can be 5%, 10%, 20%, 30%, etc.; more preferably it is 10%-25%. The mass percentage of polypropylene terephthalate is 5%-30%, for example, it can be 5%, 10%, 20%, 30%, etc.; more preferably it is 10%-25%. The mass percentage of polyethylene terephthalate is 40%-85%, for example, it can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, etc.; more preferably it is 48%-78%.
[0040] The content of PBT, PTT, and PET components determines their effective concentration in the mixture, thus affecting the actual crystallization rate and final crystallinity. PBT ensures sufficient PBT molecular chains to form a dense spherulite framework during the casting stage, constituting the micron-scale main framework of the surface layer. When the PBT content is below 5%, the spherulite structure is sparse, making it difficult for the subsequent metal layer to form effective anchorage. When the PTT content is below 5%, the gradient unevenness is not obvious, and the multi-level mechanical interlocking effect is poor. PET, as the main component, provides overall mechanical support and dimensional stability to the base film due to its high proportion, making it particularly suitable for current collector applications. When the content of PTT and PBT components differs significantly, the crystallization performance of the blend is better; when the component contents are similar, the crystallization performance is poorer. By adjusting the ratio of the three components, precise control over crystallization behavior and unevenness morphology can be achieved. When the PTT and PBT components are close, the molecular chains interpenetrate and entangle. This entanglement greatly increases the steric hindrance effect of PBT chain segment diffusion to the crystal nucleus surface and orderly arrangement. Meanwhile, as the spherulites at the growth front of PBT expand, they will continuously encounter uncrystallized PTT-rich regions, leading to a significant decrease in crystal growth rate and ultimately a reduction in overall crystallinity and imperfect crystallization.
[0041] In some preferred embodiments, the surface layer further includes a heat stabilizer comprising 0.1% to 1.0% of the surface layer mass, for example, 0.1 wt%, 0.3 wt%, 0.5 wt%, 0.8 wt%, 1.0 wt%, etc., and more preferably 0.2 to 0.5 wt%.
[0042] In an optional embodiment, the heat stabilizer is selected from at least one of trimethyl phosphate, butylated hydroxytoluene (BHT), and tridecyl phosphite.
[0043] In some preferred embodiments, the core layer further includes 0.1% to 1.0% of an antioxidant by weight of the core layer, such as 0.1 wt%, 0.3 wt%, 0.5 wt%, 0.8 wt%, 1.0 wt%, etc., and more preferably 0.3 to 0.8 wt%.
[0044] In optional embodiments, the antioxidants involved in this invention may be selected from hindered phenolic antioxidants (such as Irganox 1010), phosphite antioxidants (such as Irgafos 168), etc.
[0045] In some preferred embodiments, the intrinsic viscosity of PBT is 0.8 to 1.2 dL / g, for example, it can be 0.8 dL / g, 0.9 dL / g, 1.0 dL / g, 1.1 dL / g, 1.2 dL / g, etc.
[0046] In some preferred embodiments, the intrinsic viscosity of the PTT is 0.8~1.5 dL / g, for example, it can be 0.8 dL / g, 1.0 dL / g, 1.2 dL / g, 1.5 dL / g, etc.
[0047] In some preferred embodiments, the intrinsic viscosity of the PET is 0.6~0.75 dL / g, for example, it can be 0.6 dL / g, 0.65 dL / g, 0.7 dL / g, 0.75 dL / g, etc.
[0048] A second aspect of the present invention provides a method for preparing a base film for a composite current collector, comprising the following steps: At least two of polybutylene terephthalate, polypropylene terephthalate and polyethylene terephthalate are mixed evenly in proportion and used as the raw material for the surface layer, and then melted to obtain the surface melt. At least one of polybutylene terephthalate, polypropylene terephthalate and polyethylene terephthalate is used as the core layer material, and then melted to obtain the core layer melt. Then, the surface melt and the core melt are co-extruded in three layers and then sequentially subjected to casting, stretching and heat setting to obtain the composite current collector base film. The surface melt includes a first surface melt and a second surface melt; polybutylene terephthalate is crystallized in the casting process; and polypropylene terephthalate and polyethylene terephthalate are crystallized in the stretching and heat setting processes.
[0049] The method for preparing polymer-based films provided by this invention employs three-layer co-extrusion to ensure a clear surface / core layer interface and controllable thickness. During the preparation process, crystallization occurs in a stepwise manner following the order of PBT, PTT, and PET, avoiding phase separation and locking in a cross-scale uneven structure. Subsequent biaxial stretching and heat setting improve orientation and dimensional stability while preserving this morphology. The entire process requires no post-modification or addition of nucleating agents, is compatible with existing production lines, and offers advantages such as repeatability, mass production adaptability, and structural consistency.
[0050] The casting process includes cooling the co-extruded melt to a temperature range of 110℃-130℃ at a cooling rate of 50℃ / min-100℃ / min, and holding it at a constant temperature for 5s-15s to achieve a crystallinity of polybutylene terephthalate of 35% or higher.
[0051] In the casting process, the semi-crystallization time of polybutylene terephthalate is 0.2s-1s, the semi-crystallization time of polypropylene terephthalate is 5min-40min, and the semi-crystallization time of polyethylene terephthalate is 3min-30min.
[0052] In the stretching process, the semi-crystallization time of the poly(propylene terephthalate) is 10 min-60 min, the semi-crystallization time of the polyethylene terephthalate is 5 min-45 min, and the semi-crystallization time of the polybutylene terephthalate is 0.2 s-1 s.
[0053] In the heat setting treatment, the semi-crystallization time of the polypropylene terephthalate is 0.5 min to 4 min, the semi-crystallization time of the polyethylene terephthalate is 0.2 min to 2 min, and the semi-crystallization time of the polybutylene terephthalate is 0.1 min to 1 min.
[0054] It should be noted that the semi-crystallization time is defined as the time required for a polymer to undergo isothermal crystallization from a fully molten amorphous state at a specific temperature, reaching half of its final crystallinity (i.e., the crystallinity increases from 0 to 50% of the final equilibrium crystallinity). It reflects the rate of crystallization at that temperature: the shorter the semi-crystallization time, the faster the crystallization rate; the longer the semi-crystallization time, the slower the crystallization rate. This invention utilizes the significant differences in the semi-crystallization times of PBT, PTT, and PET across different temperature ranges to achieve staged, ordered crystallization: PBT preferentially and rapidly crystallizes fully during the casting stage at a specific temperature and time, while PTT and PET hardly crystallize at this stage. PTT and PBT only begin to crystallize extensively during specific stretching and heat-setting stages, thus forming an in-situ hierarchical crystal structure in space: spherulites (PBT, large) → zoned crystals (PTT, medium) → lamellar crystals (PET, small).
[0055] In some preferred embodiments, the first surface layer material, the core layer material, and the second surface layer material are dried before melting to reduce the moisture content of the surface layer material and the core layer material to less than 50 ppm.
[0056] In this invention, PBT, PTT, and PET are dried before use. Preferably, the drying temperature for PBT is 120℃~140℃, and the drying time is 4 hours~8 hours; the drying temperature for PTT resin is 110℃~130℃, and the drying time is 4 hours~8 hours; and the drying temperature for PET resin is 140℃~160℃, and the drying time is 4 hours~8 hours. After drying, the water content of each resin is below 50ppm, avoiding the high-temperature hydrolysis of water during melt extrusion that could lead to molecular chain breakage, thereby ensuring melt strength, stability of crystallization behavior, and consistency of the mechanical properties and surface morphology of the final film.
[0057] Furthermore, the surface melting temperature is 240℃~265℃, for example, it can be 240℃, 245℃, 250℃, 255℃, 260℃, 265℃, etc.
[0058] Preferably, the extrusion temperature for core layer melting is 265℃~280℃, for example, it can be 265℃, 268℃, 270℃, 275℃, 280℃, etc.
[0059] Preferably, the extrusion temperature of the three-layer co-extrusion is 260℃~275℃, for example, it can be 260℃, 262℃, 265℃, 270℃, 275℃, etc.
[0060] Preferably, the casting process further includes casting the semi-finished product of polybutylene terephthalate crystallization onto a quenching roller for quenching to obtain a casting sheet.
[0061] Preferably, the temperature of the quenching roller is 15℃~40℃, for example, it can be 15℃, 20℃, 25℃, 30℃, 35℃, 40℃, etc.
[0062] Rapid cooling aims to quickly cool and solidify the fully crystallized PBT casting semi-finished product, locking in the initial framework of the formed PBT spherulitic structure and surface uneven morphology; at the same time, it freezes PTT and PET in a low crystallinity state, ensuring that the crystallization of both is postponed to the subsequent stretching and heat setting stages, thereby maintaining the process controllability of PBT-PTT-PET staged sequential crystallization.
[0063] Preferably, in the stretching process, the longitudinal stretching ratio is 2.5 times to 4.0 times, for example, 2.5 times, 3.0 times, 3.5 times, 4.0 times, etc.; the transverse stretching ratio is 3.0 times to 5.0 times, for example, 3.0 times, 3.5 times, 4.0 times, 4.5 times, 5.0 times, etc.
[0064] Preferably, in the stretching process, the longitudinal stretching temperature is 45℃~80℃, for example, 45℃, 50℃, 60℃, 70℃, 80℃, etc., and the transverse stretching temperature is 85~120℃, for example, 85℃, 90℃, 100℃, 110℃, 120℃, etc.
[0065] Preferably, the heat setting treatment includes holding the stretched film semi-finished product at a constant temperature of 160℃~190℃ (e.g., 160℃, 170℃, 180℃, 190℃, etc.) for 20 seconds to 150 seconds (20 seconds, 85 seconds, 150 seconds, etc.) to obtain a base film. High temperature relaxes the molecular chain orientation stress introduced by stretching, stabilizes the formed cross-scale surface morphology, and improves the dimensional stability and thermal shrinkage consistency of the film, preventing morphology collapse or base film deformation during subsequent rolling or vapor deposition processes.
[0066] A third aspect of the present invention provides a composite current collector, the composite current collector comprising a base film and a metal layer disposed on at least one surface of the base film; the base film is a base film for composite current collectors or a base film for composite current collectors prepared by the preparation method described above.
[0067] The composite current collector provided by the present invention, in view of the advantages of the base film, enables the composite current collector using it to have high bonding strength, strong resistance to deformation and more stable performance.
[0068] In some preferred embodiments, the composite current collector is a composite aluminum foil, which is prepared by vacuum evaporating an aluminum layer on at least one side of a base film and then annealing to obtain the composite aluminum foil.
[0069] Preferably, the thickness of the aluminum layer on one side is 0.5μm to 2μm.
[0070] The method for preparing this composite aluminum foil involves directly vapor-depositing an aluminum layer onto a polymer base film with an intrinsically multi-scale uneven surface, constructing a three-level mechanical interlocking structure of nano-anchor points, submicron interlocking, and micron anchoring. During vacuum deposition, aluminum atoms penetrate into the multi-scale unevenness formed on the surface, achieving a synergistic combination of physical adsorption and multi-level mechanical interlocking, significantly enhancing the interfacial bonding force. Due to the gradient coordinated deformation of the multi-scale structure under pressure, the compaction of micron-level pits enhances anchoring, and the density of nano-level contact points increases adsorption energy.
[0071] During vacuum evaporation, aluminum atoms are deposited in gaseous form onto the surface of the polymer base film, entering the multi-scale micro-unfolds on the base film surface: Nanoscale pits: After being filled with aluminum atoms, they form high-density nano-anchors, which greatly increase the interfacial contact area and enhance physical adsorption force; Submicron-scale pits: They form medium-scale mechanical interlocks, providing the main dispersion channels for interfacial shear stress; Micron-scale pits: They form strong anchor points, undertaking the main mechanical interlocking function under 600 MPa high pressure, preventing overall interface debonding.
[0072] The synergistic effect of the three-scale mechanical interlocking structures upgrades the bonding mode between the aluminum layer and the base film from a single physical adsorption to a multiple bonding mechanism of "physical adsorption + multi-level mechanical interlocking".
[0073] Preferably, the annealing temperature is 100~150℃, for example, 100℃, 110℃, 120℃, 130℃, 140℃, 150℃, etc., to alleviate the internal stress caused by thermal stress and interfacial energy mismatch between the aluminum layer and the polymer base film during vacuum evaporation, promote the diffusion and anchoring of aluminum atoms in the surface multi-scale uneven structure, and improve the interfacial bonding strength and thermal / electrochemical cycle stability.
[0074] A fourth aspect of the present invention provides an electrode sheet comprising the aforementioned composite current collector.
[0075] A fifth aspect of the present invention provides an electrochemical device including the aforementioned electrode sheet.
[0076] Given the advantages of the composite current collectors mentioned above, the electrode sheets using them have higher compaction density adaptability, excellent rolling structure stability, and integrity of the current collector-active layer interface during cycling; the resulting electrochemical devices therefore have higher energy density, longer cycle life, better rate performance, and significantly improved safety.
[0077] The present invention is further illustrated below with specific embodiments and comparative examples. However, it should be understood that these embodiments are merely for illustrative purposes and should not be construed as limiting the invention in any way. Unless otherwise specified, the raw materials used in the embodiments and comparative examples of the present invention were carried out under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments used, unless otherwise specified, are all commercially available conventional products.
[0078] Example 1 This embodiment provides a base film for composite current collectors, and the specific preparation method is as follows: 1. PBT resin was vacuum dried at 130℃ for 6 hours; PTT resin was vacuum dried at 120℃ for 6 hours; and PET resin was vacuum dried at 150℃ for 6 hours.
[0079] 2. Surface layer to core layer ratio: The surface layer, based on 100 wt%, consists of: 20 wt% PBT, 20 wt% PTT, 59.2 wt% PET, 0.5 wt% antioxidant Irganox 1010, and 0.3 wt% heat stabilizer dibutylhydroxytoluene.
[0080] The core layer, based on 100 wt%, consists of 99.5 wt% PET and 0.5 wt% antioxidant Irganox 1010.
[0081] Take the above-mentioned proportioned surface raw materials and put them into a high-speed mixer. Mix them at 800 rpm for 8 minutes until uniform to obtain the surface ternary blend material.
[0082] Take the core layer raw materials in the above proportion and mix them at 800 rpm for 5 minutes until uniform to obtain the core layer material.
[0083] 3. Three-layer co-extrusion and casting The surface ternary blend material and the core material are fed into a three-layer co-extrusion system (die structure: A / B / A type, layer B is the core layer, and layer A is the symmetrical surface layer). The extrusion temperature gradient is set as follows: surface extruder: 255℃; core extruder: 272℃; co-extrusion die: 268℃. The surface melt and core melt are obtained by melting. The co-extruded melt is cooled to 120℃ at a cooling rate of 75℃ / min and held at a constant temperature for 10s to allow polybutylene terephthalate to fully crystallize (crystallinity ≥35%), while the crystallinity of PTT and PET is <3%. The mixture is then cast onto a quenching roller at a temperature of 30℃ to obtain a cast sheet.
[0084] 4. Stretching and heat setting After preheating, the cast film enters the longitudinal stretching unit at 90℃ with a stretching ratio of 3; then it enters the transverse stretching unit at 105℃ with a stretching ratio of 4. During the stretching process, PTT and PET begin to crystallize. After stretching, the film enters the heat setting zone at 175℃ for 85 seconds, which increases the crystallinity of PTT and PET to ≥50%. Finally, the finished base film is wound up with a thickness of 13μm (10μm core layer and 1.5μm each for the two surface layers). Among them, PBT crystallizes to form spherulites with a size of 3μm (n_PBT=3.8), PTT crystallizes to form banded crystals with a size of 550nm (n_PTT=2.6), and PET crystallizes to form lamellar crystals with a size of 75nm (n_PET=2). The spherulites and banded crystals at least partially protrude from the surface layer and together with the lamellar crystals, they form a nano-submicron-micron cross-scale uneven structure. The crystal size ratio (spherulites:banded crystals:lamellar crystals) is 40:7.3:1.
[0085] Example 2 This embodiment provides a base film for composite current collectors, which differs from Embodiment 1 in that: the core layer, based on 100 wt%, contains 99.5 wt% PTT and 0.5 wt% antioxidant.
[0086] Example 3 This embodiment provides a base film for composite current collectors, which differs from Embodiment 1 in that the surface layer formulation is different, specifically: The surface layer, based on 100 wt%, consists of: 10 wt% PBT, 25 wt% PTT, 64.2 wt% PET, 0.5 wt% antioxidant, and 0.3 wt% heat stabilizer.
[0087] In step 3, the temperature is kept constant for 10 seconds to allow polybutylene terephthalate to fully crystallize (crystallinity ≥35%), while the crystallinity of PTT and PET is <3%.
[0088] In step 4, PBT crystallizes to form spherulites with a size of 2.5 μm (n_PBT=3.5), PTT crystallizes to form zoned crystals with a size of 800 nm (nPTT=2.8), and PET crystallizes to form plate crystals with a size of 70 nm (n_PET=2.1). The crystal size ratio (spherulites:zoned crystals:plate crystals) is 35.7:11.4:1.
[0089] Example 4 This embodiment provides a base film for composite current collectors, which differs from Embodiment 1 in that the surface layer formulation is different, specifically: The surface layer, based on 100 wt%, consists of: 25 wt% PBT, 10 wt% PTT, 64.2 wt% PET, 0.5 wt% antioxidant, and 0.3 wt% heat stabilizer.
[0090] In step 3, the temperature is kept constant for 10 seconds to allow polybutylene terephthalate to fully crystallize (crystallinity ≥35%), while the crystallinity of PTT and PET is <3%.
[0091] In step 4, PBT crystallizes to form spherulites with a size of 4 μm (n_PBT=3.9), PTT crystallizes to form zoned crystals with a size of 350 nm (n_PTT=2.3), and PET crystallizes to form plate crystals with a size of 80 nm (n_PET=1.9). The crystal size ratio (spherulites:zoned crystals:plate crystals) is 50:4.4:1.
[0092] Example 5 This embodiment provides a base film for composite current collectors, which differs from Embodiment 1 in that the surface layer formulation is different, specifically: The surface layer, based on 100 wt%, consists of: 30 wt% PBT, 5 wt% PTT, 64.2 wt% PET, 0.5 wt% antioxidant, and 0.3 wt% heat stabilizer.
[0093] In step 3, the temperature is kept constant for 10 seconds to allow polybutylene terephthalate to fully crystallize (crystallinity ≥35%), while the crystallinity of PTT and PET is <3%.
[0094] In step 4, PBT crystallizes to form spherulites with a size of 4.5 μm (n_PBT=4.0), PTT crystallizes to form zoned crystals with a size of 250 nm (n_PTT=2.1), and PET crystallizes to form plate crystals with a size of 85 nm (n_PET=1.8). The crystal size ratio (spherulites:zoned crystals:plate crystals) is 52.9:2.9:1.
[0095] Example 6 This embodiment provides a base film for composite current collectors, which differs from Embodiment 1 in that the surface layer formulation is different, specifically: The surface layer, based on 100 wt%, consists of: 5 wt% PBT, 30 wt% PTT, 64.2 wt% PET, 0.5 wt% antioxidant, and 0.3 wt% heat stabilizer.
[0096] In step 3, the temperature is kept constant for 10 seconds to allow polybutylene terephthalate to fully crystallize (crystallinity ≥35%), while the crystallinity of PTT and PET is <3%.
[0097] In step 4, PBT crystallizes to form spherulites with a size of 1.5 μm (n_PBT=3.2), PTT crystallizes to form zoned crystals with a size of 900 nm (n_PTT=2.9), and PET crystallizes to form plate crystals with a size of 65 nm (n_PET=2.2). The crystal size ratio (spherulites:zoned crystals:plate crystals) is 23.1:13.8:1.
[0098] Example 7 This embodiment provides a base film for composite current collectors, which differs from Embodiment 1 in that the surface layer formulation is different, specifically: The surface layer, based on 100 wt%, consists of: 20 wt% PBT, 79.2 wt% PET, 0.5 wt% antioxidant, and 0.3 wt% heat stabilizer; In step 3, the temperature is kept constant for 10 seconds to allow polybutylene terephthalate to fully crystallize (crystallinity ≥35%), while the crystallinity of PTT and PET is <3%.
[0099] In step 4, PBT crystallizes to form spherulites with a size of 2.8 μm (n_PBT=3.6), and PET crystallizes to form lamellar crystals with a size of 80 nm (n_PET=2.0), with a crystal size ratio (spherulites:lamellae) of 35:1.
[0100] Example 8 This embodiment provides a base film for composite current collectors, which differs from Embodiment 1 in that the surface layer formulation is different, specifically: The surface layer, based on 100 wt%, consists of: 20 wt% PTT, 79.2 wt% PET, 0.5 wt% antioxidant, and 0.3 wt% heat stabilizer. In step 3, no constant temperature stay is performed.
[0101] In step 4, PTT crystallizes to form a ring-shaped crystal with a size of 600 nm (n_PTT=2.7), and PET crystallizes to form a plate-shaped crystal with a size of 72 nm (n_PET=2.1). The crystal size (ring-shaped crystal: plate-shaped crystal) is 8.3:1.
[0102] Example 9 This embodiment provides a base film for composite current collectors, which differs from Embodiment 1 in that the surface layer formulation is different, specifically: The surface layer, based on 100 wt%, comprises: 49.6 wt% PBT, 49.6 wt% PET, 0.5 wt% antioxidant, and 0.3 wt% heat stabilizer; In step 3, the temperature is kept constant for 10 seconds to allow polybutylene terephthalate to fully crystallize (crystallinity ≥35%), while the crystallinity of PTT and PET is <3%.
[0103] In step 4, PBT crystallizes to form spherulites with a size of 5.0 μm (n_PBT=4.0), and PET crystallizes to form lamellar crystals with a size of 90 nm (n_PET=1.6), with a crystal size (spherulite:lamellar) ratio of 55.6:1.
[0104] Example 10 This embodiment provides a base film for composite current collectors, which differs from Embodiment 1 in that the surface layer formulation is different, specifically: The surface layer, based on 100 wt%, consists of: 49.6 wt% PTT, 49.6 wt% PET, 0.5 wt% antioxidant, and 0.3 wt% heat stabilizer. In step 3, a constant temperature stay was not performed.
[0105] In step 4, PTT crystallizes to form a ring-shaped crystal with a size of 650 nm (n_PTT=2.8), and PET crystallizes to form a plate-shaped crystal with a size of 68 nm (n_PET=2.2). The ratio of crystal size (ring-shaped crystal: plate-shaped crystal) is 9.6:1.
[0106] Example 11 This embodiment provides a base film for composite current collectors, which differs from Embodiment 1 in that: In step 3, the co-extruded melt is cooled to a temperature range of 130°C at a cooling rate of 50°C / min, and held at a constant temperature for 5 seconds to allow polybutylene terephthalate to fully crystallize (crystallinity ≥35%); the temperature of the quenching roller is 15°C. In step 4, the cast film is preheated and then enters the longitudinal stretching unit: temperature 45℃, stretching ratio 2.5 times; then it enters the transverse stretching unit: temperature 120℃, stretching ratio 3 times; after stretching, the film enters the heat setting zone: set at 160℃ for 150s, so that the crystallinity of PTT and PET is increased to ≥50%, and finally the finished base film is wound up with a thickness of 13μm (core layer 10μm, double surface layer 1.5μm each). Among them, PBT crystallizes to form spherulites with a size of 3.2μm (n_PBT=3.7), PTT crystallizes to form banded crystals with a size of 520nm (n_PTT=2.5), and PET crystallizes to form lamellar crystals with a size of 78nm (n_PET=2.0). The crystal size (spherulites:banded crystals:lamellae) is 41:6.7:1.
[0107] Example 12 This embodiment provides a base film for composite current collectors, which differs from Embodiment 1 in that: In step 3, the co-extruded melt is cooled to a temperature range of 110°C at a cooling rate of 100°C / min, and held at a constant temperature for 15 seconds to allow polybutylene terephthalate to fully crystallize (crystallinity ≥35%); the temperature of the quenching roller is 40°C. In step 4, the cast film is preheated and then enters the longitudinal stretching unit: temperature 80℃, stretching ratio 4 times; then it enters the transverse stretching unit: temperature 85℃, stretching ratio 5 times; after stretching, the film enters the heat setting zone: set at 190℃ for 20s, so that the crystallinity of PTT and PET is increased to ≥50%, and finally the finished base film is wound up with a thickness of 13μm (core layer 10μm, double surface layer 1.5μm each). Among them, PBT crystallizes to form spherulites with a size of 2.8μm (n_PBT=3.6), PTT crystallizes to form banded crystals with a size of 580nm (n_PTT=2.6), and PET crystallizes to form lamellar crystals with a size of 72nm (n_PET=2.1). The crystal size (spherulites:banded crystals:lamellae) is 38.9:8.1:1.
[0108] Comparative Example 1 This comparative example provides a base film for composite current collectors, which differs from Example 1 in that: the surface layer, based on 100 wt%, contains: 99.2 wt% PBT, 0.5 wt% antioxidant, and 0.3 wt% heat stabilizer.
[0109] Comparative Example 2 This comparative example provides a base film for composite current collectors, which differs from Example 1 in that: the surface layer, based on 100 wt%, contains: 99.2 wt% PTT, 0.5 wt% antioxidant, and 0.3 wt% heat stabilizer.
[0110] Comparative Example 3 This comparative example provides a base film for composite current collectors, which differs from Example 1 in that: the surface layer, based on 100 wt%, comprises: 99.2 wt% PET, 0.5 wt% antioxidant, and 0.3 wt% heat stabilizer.
[0111] Comparative Example 4 Compared to Example 1, step 3 did not involve a constant temperature stay.
[0112] Application Example 1-12 and Comparative Application Example 1-4 The composite current collectors obtained in Examples 1-12 and Comparative Examples 1-4 were subjected to plasma cleaning (O2 atmosphere, power 200W, time 60s) to remove surface organic contaminants from the base film; under a vacuum of 5×10 -2 Under Pa conditions, aluminum layers were deposited on both sides by resistance evaporation at a rate of 1.5 nm / s and the deposition time was controlled until the aluminum layer thickness was 1.0 ± 0.1 μm. After evaporation, the aluminum layer was annealed at 120 °C for 10 min to obtain composite aluminum foil.
[0113] Test Example 1 The composite aluminum foils obtained from the application examples and comparative application examples were subjected to performance tests, including interfacial bonding strength tests and electrolyte resistance tests.
[0114] The interface bonding strength test was conducted using the tape peeling method: the sample was cut into strips 20mm wide and longer than 100mm. One side of the strip was attached to the SUS steel plate with double-sided PET tape. Then, commercially available standard 20mm wide tape (Nitto tape) was attached to the side of the strip to be tested (the length should be longer than the strip). A 2kg rubber roller was used to roll and press the strip back and forth three times. Finally, a 180° peel test (bonding force) was performed on the peel tester. The test conditions were 300mm / min.
[0115] Electrolyte resistance test: Cut the sample into 50mm×100mm pieces, place the pieces in a plastic test box in a glove box, pour about 61g of electrolyte into the test box to immerse the pieces, and place the sealed plastic test box in an 85℃ oven for 15 days; after immersion, take out the sample in a fume hood, rinse and wipe with water and alcohol in turn to remove electrolyte residue, and after the sample dries, perform the bonding strength test using the same bonding strength test method as above.
[0116] The specific formulation of the electrolyte is as follows: 1 mol / L LiPF6 (lithium hexafluorophosphate) is dissolved in a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC), with the volume ratio of the three solvents being EC:DMC:EMC=1:1:1.
[0117] The test data is recorded in Table 1.
[0118] Table 1
[0119] As shown in Table 1, this invention utilizes three polyesters with different numbers of methylene groups in their alcohol segments (4 for PBT, 3 for PTT, and 2 for PET), exhibiting a clear gradient in crystallization rate: PBT (fastest) > PTT (medium) > PET (slowest). A specific process design is used for staged crystallization: in the casting stage, the temperature is controlled at 110-130℃ and held for 5-15 seconds to ensure PBT crystallinity ≥35%, while PTT / PET crystallinity <3%. In the stretching and heat-setting stages, the crystallinity of PTT and PET is induced to increase to ≥50%, ensuring the final crystal size ratio satisfies spherulite:zone crystal:lamellar crystal = (10-100):(1-20):1, avoiding macroscopic voids or excessive structural crowding, making it particularly suitable for high-compact systems. Spherulites act as rivet anchors, providing vertical tensile strength; zone crystals convert shear stress into circumferential dissipated energy, improving crack resistance; and lamellar crystals increase contact area and chemical affinity sites, enhancing metal nucleation density and wettability.
[0120] Specifically, the initial interfacial bonding strength and strength retention rate after immersion of Application Examples 1-12 are superior to those of Comparative Application Examples 1-4, confirming the fundamental improvement of interfacial bonding and chemical resistance by the multi-scale mechanical interlocking structure synergistically constructed by PBT spherulite anchoring, PTT annular crystal stress dissipation, and PET sheet crystal nano-adhesion. Among them, the performance of Application Examples 7-10, which only contain two components, is significantly weaker than that of Application Examples 1-6, which are ternary blend systems. In contrast, Comparative Application Examples 1-4, due to the use of a single component or the absence of a staged isothermal residence process, cannot form a multi-level crystal structure, resulting in a significant decrease in bonding strength and electrolyte resistance.
[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A base membrane for composite current collectors, characterized in that, The base film comprises a surface layer and a core layer. The surface layer comprises a blend of at least two of polybutylene terephthalate, polypropylene terephthalate, and polyethylene terephthalate. The core layer comprises at least one of polybutylene terephthalate, polypropylene terephthalate, and polyethylene terephthalate. The preparation of the base film comprises sequential casting, stretching, and heat setting. The polybutylene terephthalate crystallizes to form spherulites during the casting process, the polypropylene terephthalate crystallizes to form banded crystals during the stretching and heat-setting processes, and the polyethylene terephthalate crystallizes to form lamellar crystals during the stretching and heat-setting processes; the crystal size ratio of the spherulites, banded crystals, and lamellar crystals is (10-100):(1-20):1; at least two of the spherulites, banded crystals, and lamellar crystals at least partially protrude from the surface of the surface layer to form an uneven structure.
2. The composite current collector base film according to claim 1, characterized in that, In the casting process, polybutylene terephthalate has at least 35% crystallinity, and polypropylene terephthalate and / or polyethylene terephthalate have less than 3% crystallinity; and / or, In the stretching treatment and the heat setting treatment, the polypropylene terephthalate and the polyethylene terephthalate have a crystallinity of at least 50%; and / or, The crystal structure formed by the crystallization of polybutylene terephthalate is a spherulite with an n_PBT ratio of 3-4, and a crystal size of 1μm-5μm; and / or, The crystal structure formed by the crystallization of polypropylene terephthalate is a ring-zoned crystal with an n_PTT of 2-3, and the crystal size is 100nm-1000nm; The crystal structure formed by the crystallization of polyethylene terephthalate is a lamellar crystal with n_PET of 1.5-2.5 and a crystal size of 50nm~100nm.
3. The composite current collector base film according to claim 1, characterized in that, In the surface layer, the mass ratio of polybutylene terephthalate to polypropylene terephthalate is 1:(0.15-6); and / or, The mass ratio of polybutylene terephthalate to polyethylene terephthalate is 1:(1-18); and / or, the mass ratio of polypropylene terephthalate to polyethylene terephthalate is 1:(1-18).
4. The composite current collector base film according to claim 1, characterized in that, The surface layer is a ternary blend of polybutylene terephthalate, polypropylene terephthalate, and polyethylene terephthalate; and / or, The surface layer includes a first surface layer and a second surface layer, the thickness of which is independently 10%-20% of the thickness of the base film; and / or, The thickness of the base film is 2μm~15μm; and / or, The surface layer also includes 0.1% to 1.0% antioxidant by weight of the surface layer; and / or, The surface layer further includes a heat stabilizer comprising 0.1% to 1.0% of the surface layer mass; and / or, The core layer also includes an antioxidant comprising 0.1% to 1.0% of the core layer mass.
5. The composite current collector base film according to claim 4, characterized in that, The surface layer comprises, by 100% by mass, 5%-30% polybutylene terephthalate, 5%-30% polypropylene terephthalate, and 40%-85% polyethylene terephthalate.
6. A method for preparing a composite current collector base film according to any one of claims 1-5, characterized in that, The preparation method includes the following steps: At least two of polybutylene terephthalate, polypropylene terephthalate and polyethylene terephthalate are mixed evenly in proportion and used as the raw material for the surface layer, and then melted to obtain the surface melt. At least one of polybutylene terephthalate, polypropylene terephthalate and polyethylene terephthalate is used as the core layer material, and then melted to obtain the core layer melt. Then, the surface melt and the core melt are co-extruded in three layers and then sequentially subjected to casting, stretching and heat setting to obtain the composite current collector base film. The surface melt includes a first surface melt and a second surface melt; polybutylene terephthalate is crystallized in the casting process; and polypropylene terephthalate and polyethylene terephthalate are crystallized in the stretching and heat setting processes.
7. The preparation method according to claim 6, characterized in that, The casting process includes cooling the co-extruded melt to a temperature range of 110°C-130°C at a cooling rate of 50°C / min-100°C / min, holding it at that temperature for 5s-15s to achieve a crystallinity of polybutylene terephthalate of 35% or higher; and / or, In the casting process, the semi-crystallization time of polybutylene terephthalate is 0.2s-1s, that of polypropylene terephthalate is 5min-40min, and that of polyethylene terephthalate is 3min-30min; and / or, In the stretching process, the semi-crystallization time of the polypropylene terephthalate is 10 min-60 min, the semi-crystallization time of the polyethylene terephthalate is 5 min-45 min, and the semi-crystallization time of the polybutylene terephthalate is 0.2 s-1 s; and / or, In the heat setting treatment, the semi-crystallization time of the polypropylene terephthalate is 0.5 min to 4 min, the semi-crystallization time of the polyethylene terephthalate is 0.2 min to 2 min, and the semi-crystallization time of the polybutylene terephthalate is 0.1 min to 1 min.
8. The preparation method according to claim 6, characterized in that, Before melting, the first surface layer material, the core layer material, and the second surface layer material are dried to ensure that the moisture content of the surface layer material and the core layer material is less than 50 ppm. Preferably, the drying temperature of the polybutylene terephthalate is 120℃~140℃, and the drying time is 4 hours~8 hours; Preferably, the drying temperature of the polypropylene terephthalate is 110℃~130℃, and the drying time is 4 hours~8 hours; Preferably, the drying temperature of the polyethylene terephthalate is 140℃~160℃, and the drying time is 4 hours~8 hours.
9. The preparation method according to claim 7, characterized in that, The melting temperature of the surface layer is 240℃~265℃; Preferably, the melting temperature of the core layer is 265℃~280℃; Preferably, the extrusion temperature of the three-layer co-extrusion is 260℃~275℃; Preferably, the casting process further includes casting the semi-finished product of polybutylene terephthalate after full crystallization onto a quenching roller for quenching to obtain a casting sheet; Preferably, the temperature of the quenching roller is 15°C to 40°C; Preferably, in the stretching process, the longitudinal stretching ratio is 2.5 to 4.0 times, and the transverse stretching ratio is 3.0 to 5.0 times; Preferably, in the stretching process, the longitudinal stretching temperature is 45℃~80℃, and the transverse stretching temperature is 85℃~120℃. Preferably, the heat setting process includes holding the stretched film semi-finished product at a constant temperature of 160°C to 190°C for 20 to 150 seconds to obtain a base film.
10. A composite current collector, characterized in that, The composite current collector includes a base film and a metal layer disposed on at least one surface of the base film; the base film is the composite current collector base film according to any one of claims 1 to 5 or the composite current collector base film prepared by the preparation method according to any one of claims 6 to 9.
11. An electrode sheet, characterized in that, Includes the composite current collector as described in claim 10.
12. An electrochemical device, characterized in that, Includes the electrode sheet as described in claim 11.